Studies on batch formulation of a kit for the preparation of the 99mTc-Ubiquicidin (29-41): An infection imaging agent. (January 2016) - Arjun, Chanda; Mukherjee, Archana; Bhatt, Jyotsna; Chaudhari, Pradip; Repaka, Krishna Mohan; Venkatesh, Meera; Samuel, Grace
Abstract: The aim of this study was to formulate an indigenous cold kit of Ubiquicidin, UBI (29-41), for easy preparation of 99m Tc-UBI (29-41) to be used as an infection imaging agent. A two component kit with the peptide and SnCl2 as vial 1 and optimum amount of NaOH as vial 2 was successfully formulated as seen from the consistent radiochemical and pharmaceutical purity of the product over six consecutive batches of kits. The utility of the kit could be demonstrated through in-vitro and in vivo specificity of 99m Tc-UBI (29-41). Highlights: An indigenous cold kit of Ubiquicidin, UBI (29–41), for preparation of 99m Tc-UBI (29-41) for infection imaging was formulated. Simple ITLC method to calculate yield of 99m Tc-UBI (29-41) complex was established. Consistent batch production of UBI kit with acceptable criteria was demonstrated.